Development of a laboratory test to characterise the behaviour of free gold for use in a combined flash flotation and gravity concentrator model - McGrath, Teresa; Staunton, William; Eksteen, Jacques (Elsevier, 2013)
Currently there is no process model which simulates the behaviour of gravity recoverable gold (GRG) in flash flotation unit operation. Once developed, such a flash float model could be incorporated into an existing model for gravity concentration. Together, the integrated gravity recovery-flash float model will provide a tool for predicting the recovery of GRG in a closed milling circuit using both batch centrifugal concentration and flash flotation. In order to design a flash flotation model, a reliable laboratory method to characterise the response of GRG when subjected to flash flotation conditions has been developed. This paper details the evaluation of the effects of various chemical (reagent concentrations, sulfide presence, etc.) and operational (airflow, agitation, etc.) parameters on the overall GRG recovery by lab scale flash flotation. Of the factors evaluated, free gold flotation was found to be most impacted by potassium amyl xanthate (PAX) and copper sulfate reagent levels, as well as agitation speed and sulfide mineral additions.